The Effect of Season and The Implications For Sustainable Fisheries on The Catch Results of Yellowfin Tuna In Indonesia - Bayu Arif Pasa Laksmana; Yayan Hernuryadin; Yasman Yasman (Pelopor Publikasi Akademika, 2024)
This study assessed the purse seine, handline and pole and line catches at PPS (Samudera Fishing Port Kendari) specifically targeting skipjack and yellowfin tuna in the Banda Sea. Although there has been a rise in tuna output over the past two years, the examination of fish size in September until November revealed substantial fluctuation. Additionally, the implementation of the moratorium policy had a detrimental effect. Ensuring the sustainability of fisheries in the Banda Sea, particularly for large pelagic fish like skipjack and yellowfin tuna, necessitates the implementation of adaptive management and selective fishing practices, with a particular focus on enforcing mesh size regulations. The aims of this study were to examine the patterns of tuna fisheries landing at PPS, specifically focusing on the sorts of catches made using purse seine, handline, and pole and line fishing methods. Additionally, the study aimed to assess the length frequency distribution of Thunnus albacares caught using purse seine, handline, and pole and line fishing gear. The methodology offers a thorough framework for eval_uating the sustainability of Thunnus albacares fisheries in PPS Kendari. Policymakers can develop effective management plans for long-term resource sustainability by assessing catch composition, productivity, and size distribution across various fishing gears. The analysis of this study conducted in September - November 2023 revealed that the fish catches varied in size, ranging from 13 cmFL to 124 cmFL.